(untitled) (Praxis Educativa, 2026)
The objective of this article is to analyze the motivational and behavioral factors associated with the quality of student life among middle school students in the city of San Fernando del Valle de Catamarca (Argentina) during 2024. A quantitative, non-experimental, correlational, and cross-sectional study was conducted, based on data from the Planet Youth Survey. Quality of student life was measured using a synthetic well-being index, while the independent variables included attitudinal indicators regarding the school experience and a synthetic absenteeism index constructed through factor analysis. The analytical strategy consisted of ordinal logistic regression. The results show that school absenteeism is negatively and statistically significantly associated with quality of student life, while certain negative attitudes toward studying present a consistent theoretical direction, although without statistical significance. It is concluded that school behaviors and motivational dispositions jointly influence educational well-being, providing useful evidence for the design of pedagogical and territorial policies aimed at improving the school experience.